Pelatihan Menulis Cerpen Bermuatan Budaya Lokal Untuk Siswa SMK Darussalam Karangpucung - Agnes Apryliana; Helmi Seftiani; Dini Nurhayati (Universitas Muhammadiyah Manado, 2022)
This community service project aims to train students of SMK Darussalam Karangpucung in writing short stories that contain local culture. This project recognizes the challenges students face in writing short stories, including difficulties in generating ideas and a lack of interest and motivation. Traditional teaching methods focus on lectures and analyzing existing stories, leading to a lack of hands-on experience and boredom. The project implements a five-step approach: preparation, pre-activity surveys, material delivery, writing practice, and question and answer sessions. The material presented includes the essence of short stories, their components (intrinsic and extrinsic elements), imagination techniques, writing tips, and the integration of cultural elements. The students enthusiastically participated in a short story writing practice session with the theme